PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN MODAL INTELEKTUAL PADA NILAI PERUSAHAAN - Rahayu Dewi, Ni Luh Putu Sri; Harta Mimba, Ni Putu Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
The main goal of companies that have gone public in general is to maximize the value of the company which can be seen from the high share price. This study aims to determine the effect of corporate social responsibility disclosure and intellectual capital on firm value. This research was conducted on the Indonesia Stock Exchange (IDX) with a research period of 2017-2019. The population of this research are all trading, service and investment sector companies listed on the Indonesia Stock Exchange in 2017-2019 which disclose annual reports and corporate social responsibility of 90 companies. The number of samples used in this study was obtained as many as 22 companies with 56 samples (observations). The sample selection in this study used a non-probability sampling method with a purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The results of the study partially show that corporate social responsibility disclosure has a negative effect on firm value. While intellectual capital has no effect on the value of the company.